Why poor logging practices persist in the tropics - Putz, F.E.; Dykstra, D.P.; Heinrich, R. (2000)
Despite abundant evidence that both the environment damage and the financial costs of logging can be reduced substantially by training workers, pre-planning skid trails, practicing directional felling, and carrying out a variety of other well-known forestry practices, destructive logging is still common in the tropics. Based on collective experience with loggers in tropical forests, seven possible reasons for this seemingly irrational behaviour are discussed. The principal reason for poor logging practices is apparently that the widely heralded cost savings associated with reduced-impact logging relative to unplanned logging by un-trained crews may not be realised under some conditions. In particular, where compliance with logging guidelines restricts access to steep slopes or prohibits ground-based timber yarding on wet ground, reduced-impact logging may be synonymous with reduced-income logging. Given that under such conditions loggers may not adopt reduced-impact logging methods out of self-interest, fiscal mechanisms for promoting sustainable forest management may be needed.